Effect of hydrogen peroxide on prostaglandin production and cellular integrity in cultured porcine aortic endothelial cells. - Whorton, A R (1985)
Oxidative damage to the vascular endothelium may play an important role in the pathogenesis of atherosclerosis and aging, and may account in part for reduced vascular prostacyclin (PGI2) synthesis associated with both conditions. Using H2O2 to induce injury, we investigated the effects of oxidative damage on PGI2 synthesis in cultured endothelial cells (EC). Preincubation of EC with H2O2 produced a dose-dependent inhibition (inhibitory concentration [IC50] = 35 microM) of PGI2 formation from arachidonate. The maximum dose-related effect occurred within 1 min after exposure although appreciable H2O2 remained after 30 min (30% of original). In addition, H2O2 produced both a time- and dose-dependent injury leading to cell disruption, lactate dehydrogenase release, and 51Cr release from prelabeled cells. However, in dramatic contrast to H2O2 effects on PGI2 synthesis, loss of cellular integrity required doses in excess of 0.5 mM and incubation times in excess of 1 h. The superoxide-generating system, xanthine plus xanthine oxidase, produced a similar inhibition of PGI2 formation. Such inhibition was dependent on the generation of H2O2 but not superoxide in that catalase was completely protective whereas superoxide dismutase was not. H2O2 (50 microM) also effectively inhibited basal and ionophore A23187 (0.5 microM)-stimulated PGI2 formation. However, H2O2 had no effect on phospholipase A2 activity, because ionophore A23187-induced arachidonate release was unimpaired. To determine the effects on cyclooxygenase and PGI2 synthase, prostaglandin products from cells prelabeled with [3H]arachidonate and stimulated with ionophore A23187, or products formed from exogenous arachidonate were examined. Inhibition of cyclooxygenase but not PGI2 synthase was observed. Incubation of H2O2-treated cells with prostaglandin cyclic endoperoxide indicated no inhibition of PGI2 synthase. Thus, in EC low doses of H2O2 potently inhibit cyclooxygenase after brief exposure whereas larger doses and prolonged exposure are required for classical cytolytic effects. Surprisingly, PGI2 synthase, which is known to be extremely sensitive to a variety of lipid peroxides, is not inhibited by H2O2. Lipid solubility, enzyme location within the EC membrane, or the local availability of reducing factors may explain these results, and may be important determinants of the response of EC to oxidative stress.